NEUROLOGICAL COMPLICATION OF HYPEREMESIS GRAVIDARUM IN PREGNANCY: A CASE-BASED REVIEW (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Pregnancy related hyperemesis gravidarum is a severe form of nausea and vomiting that can result in vitamin deficiency, electrolyte imbalance, dehydration and malnutrition. Severe neurological complication are rare in obstetric practice but they can be fatal if left untreated Background: A significant neurological consequence of thiamine deficiency brought on by prolonged vomiting is wernicke’s encephalopathy. In severe cases osmotic demyelination syndrome, including central pontine myelinolysis, may also be caused by related metabolic abnormalities and quick correction of chronic hyponatremia. To lower maternal morbidity and enhance results, early detection of these issue is crucial. Objective: To review the neurological complication associated with hyperemesis gravidarum, with special emphasis on wernicke’s encephalopathy and central pontine myelinolysis and to highlight their clinical significance using a brief case based illustration. Material and Method: Using pertinent published research on osmotic demyelination syndrome, wernicke’s encephalopathy and hyperemesis gravidarum a narrative review was created. The pathophysiology, clinical presentation, diagnostic approach, neuroimaging findings, management principles and preventive strategies were discussed using previous published literature and an illustrative published clinical case. Result: According to the review, prolonged vomiting in hyperemesis gravidarum can cause serious metabolic and nutrition problem, especially electrolyte imbalance and thiamine deficiency. Serious neurological issue like central pontine myelinolysis and wernicke’s encephalopathy can arise from these anomalies. Timely neuroimaging, cautious electrolyte correction and early thiamine supplementation and crucial for diagnosis and treatment. Conclusion: Although they are uncommon, neurological complication from hyperemesis gravidarum can cause serious maternal morbidity if diagnosis is delayed. Preventing irreversible neurological damage and improving material outcomes require a high index of suspicion timely thiamine administration careful correction of metabolic abnormalities and early neuroimaging.